AB0426 FIBROSING INTERSTITIAL LUNG DISEASE IN PRIMARY SJOGREN SYNDROME. (13th June 2020) - Manfredi, A.; Vacchi, C.; Della Casa, G.; Cerri, S.; DI Cecco, G.; Coppi, F.; Luppi, F.; Salvarani, C.; Sebastiani, M.
Abstract : Background: Interstitial lung disease (ILD) represents the most frequent pulmonary manifestation of primary Sjogren's syndrome (pSS), with a prevalence ranging between 6-70% in different retrospectives studies. Non-specific interstitial pneumonia (NSIP) is recognized as the most common ILD disorder, followed by organizing pneumonia (OP), usual interstitial pneumonia (UIP) and lymphocytic interstitial pneumonia (LIP), specifically associated with pSS but less frequent. Objectives: To investigate the prevalence of fibrosing patterns in a monocentric cohort of pSS patients evaluated for lung involvement in a cross-sectional study. Methods: In a cross-sectional study all patients fulfilling ACR/EULAR classification criteria for pSS and with a known diagnosis of ILD were enrolled; the other patients were carefully investigated for signs or symptoms suggestive for ILD (including the search for velcro crackles with a digital device); when suspect, patients underwent to high resolution computed tomography (HRCT). An expert radiologist re-evaluated all HRCT for classifying the ILD pattern as: UIP, fibrotic NSIP, fibrotic OP, NSIP, OP, LIP, indeterminate. Results: One hundred and eighty-five pSS patients were enrolled; among them 34 showed ILD (18.4%) with the following features: M/F 3/31, median age 57 (range 24-80), median FVC 90% (39-127%), median DLCO 49% (20-84%). Patients were classified in two groups according to radiologic classification: the group 1 (18 pts 52, 9%) included UIP (13 patients, 38.2%), fibrotic NSIP (4, 11.8%), fibrotic OP (1 2.9%); the group 2 (16 pts, 47.1%) included NSIP (6, 17.6%), OP (4, 11.8%), indeterminate (4, 11.8%), LIP (2, 5.9%). No significant differences were observed between the two groups with the exception of anti-SSB positivity more frequently detected in non-fibrosing pattern (p 79 1 0 0, 79 1 043 043 ). Conclusion: Despite previous observations, our data suggest a high prevalence of fibrosing ILD pattern in pSS patients. We participate at a multidisciplinary team with expert pulmonologists and radiologists and some patients of our cohort firstly referred to pulmonologist for appearance of ILD before the diagnosis of pSS, contributing to the possible selection of more severe lung disease. However, these data suggest first of all that pSS should always be considered in differential diagnosis of fibrosing ILD; moreover, since fibrosing ILD is thought to have a worse response to immunosuppressive drugs, the role of new possible therapeutic strategies such as anti-fibrotic could represent an important field of interest. Disclosure of Interests: None declared